2013
DOI: 10.3390/ijms141019618
|View full text |Cite
|
Sign up to set email alerts
|

A Combination of Pre- and Post-Exposure Ascorbic Acid Rescues Mice from Radiation-Induced Lethal Gastrointestinal Damage

Abstract: The development of an effective therapy for radiation-induced gastrointestinal damage is important, because it is currently a major complication of treatment and there are few effective therapies available. Although we have recently demonstrated that pretreatment with ascorbic acid attenuates lethal gastrointestinal damage in irradiated mice, more than half of mice eventually died, thus indicating that better approach was needed. We then investigated a more effective therapy for radiation-induced gastrointesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 32 publications
3
35
0
1
Order By: Relevance
“…The in vivo radioprotective properties of AA have been well demonstrated in several reports (3)(4)(5). In the present study, the in vivo radioprotective effects of EC in mouse blood cells were investigated.…”
Section: In Vivo Radioprotection Of Mouse Platelets By Pre-and Postrasupporting
confidence: 52%
See 1 more Smart Citation
“…The in vivo radioprotective properties of AA have been well demonstrated in several reports (3)(4)(5). In the present study, the in vivo radioprotective effects of EC in mouse blood cells were investigated.…”
Section: In Vivo Radioprotection Of Mouse Platelets By Pre-and Postrasupporting
confidence: 52%
“…Postradiation treatment with ascorbic acid (AA) is reportedly effective in mitigating radiation lethality in mice after whole body irradiation at 7.5 Gy (3). In addition, radiation-induced lethal gastrointestinal damage as well as radiation injury to bone marrow cells were reduced by treatment with AA ABBREVIATIONS: DCm, mitochondrial membrane potential; AA, ascorbic acid; ATM, ataxia telangiectasia mutated; DCFDA, 2',7'-dichlorofluorescin diacetate; DSB, double-strand break; EC, epicatechin; H2AX, H2A histone family, member X; IR, ionizing radiation; mtDNA, mitochondrial DNA; NAC, N-acetyl-L-cysteine; Nrf2, nuclear factor erythroid 2-related factor 2; oxphos, oxidative phosphorylation; ROS, reactive oxygen species; SOD, superoxide dismutase; Tempo, 2,2,6,6-tetramethyl-1-piperidinyloxy; TOC, a-tocophenol; WBC, white blood cell; WT, wild type (4,5). Epicatechin (EC), a component of green tea extract, is reported to scavenge radiation-induced reactive oxygen species (ROS) and has a radioprotective effect in human cells as well as biologic models of zebrafish and mice (6)(7)(8)(9).…”
mentioning
confidence: 99%
“…Addition of pharmacological ascorbate partially reversed the decreases in both the 10 Gy and 13 Gy groups of mice suggesting that ascorbate may protect the gastrointestinal tract from the damaging effects of IR. Additionally, previous studies have demonstrated that radiation-induced jejunal toxicity was accompanied by increases in serum tumor necrosis factor-α (TNF-α) ( 34 ). TNF-α was 7.5 ± 2.2 pg/ml in controls and was increased to 25.0 ± 1.5 pg/ml after 13 Gy.…”
Section: Resultsmentioning
confidence: 99%
“…Ito et al studied the effects of ascorbic acid administration in preventing RIGD in mice, reporting that administration of ascorbic acid 3 days prior to radiation exposure, followed by another dose 8 hours before exposure, followed by continued administration for 7 days after radiation exposure was associated with a 100% survival rate. This compared to a maximum of 20% survival rate in mice treated with ascorbic acid 3 days prior to radiation exposure, those treated with a single dose 8 hours before exposure or those treated post-exposure [4]. Blockade of p53 is not a viable strategy for prevention of RIGD since p53 maintains genomic stability.…”
Section: Oxidative Stressmentioning
confidence: 99%